RANCANG BANGUN SISTEM INFORMASI PERENCANAAN PRODUKSI PADA PERUSAHAAN PERCETAKAN CV.OKTA MENGGUNAKAN METODE PROTOTYPE - Mochamad Fauzil Adim; Dwanoko, Yoyok Seby; Setiyaningsih, Wiji (Department of System Information, 2025)
CV. OKTA is a printing company engaged in packaging production. The company faces several issues, including poor recording of customer orders, lack of proper tracking of raw materials used during the production process, and unrecorded production outputs. These problems can disrupt production activities and potentially lead to significant losses if not addressed. To overcome these challenges, an Information System was developed using the Prototype Method, which involves thorough analysis to gather requirements and generate system concepts. This method includes five main stages: Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, and Deployment Delivery & Feedback. The resulting Production Process Information System can be accessed by Admin, PPIC, Operator, and Owner, with all stages from start to finish being recorded in the system. The system was developed using the PHP programming language and Laragon as the database environment. The results of the study show that the system functions effectively and supports the operations of CV. OKTA, achieving an average User Acceptance Test (UAT) score of 93.23%.